Osteogenesis imperfecta in combination with Graves disease - Marina S. Sheremeta; Ekaterina A. Pigarova; Kristina S. Kulikova; Irina M. Belovalova; Anatoliy N. Tyulpakov; Pavel O. Rumiantsev (Ожирение и метаболизм, 2017)
Osteogenesis imperfecta (OI) – is a group of genetically disorders, which are charaterized by a disturbed bone formation. In turn, the excess of thyroid hormones in Graves' disease (GD) also posses a negative effect on bone tissue, thereby aggravating OI. That requires from the endocrinologist the most careful management of patients with the combination of these pathologies. In this article, we present a unique clinical case of a combination of GD and OI.